2019
DOI: 10.3390/molecules24101904
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Biological Activities of Oregano Essential Oil and Its Fractions Obtained by Vacuum Distillation

Abstract: Oregano (Poliomintha longiflora) essential oil (Ooil) is a product of high commercial value and many applications, including chemotherapy. Aiming to achieve the best use of this resource, the present study focuses on the characterization of separated fractions of Ooil by fractional vacuum distillation at low pressure. Four fractions (F1–F4) and undistilled oil (Unoil) were separated from Ooil and analyzed for their chemical composition and biological activities, such as antioxidant and antimicrobial activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 38 publications
6
33
0
Order By: Relevance
“…On the other hand, the EO of oregano is composed mainly of carvacrol (59.82%), c-terpinene (10.85%), and α-pinene (9.89%), which account for about three-quarters of the total chemical composition accompanied by other constituents with relatively low contents. Similar results were found by Rostro-Alanis et al for oregano EO whose majority compound is carvacrol with a higher concentration of 60.03% [33]. ere is a slight difference in the chemical composition of the main components of the two EOs with those of literature studies, and this may be due to abiotic factors such as the specific climate of the origin regions of the samples.…”
Section: Chemical Composition Of Eossupporting
confidence: 87%
“…On the other hand, the EO of oregano is composed mainly of carvacrol (59.82%), c-terpinene (10.85%), and α-pinene (9.89%), which account for about three-quarters of the total chemical composition accompanied by other constituents with relatively low contents. Similar results were found by Rostro-Alanis et al for oregano EO whose majority compound is carvacrol with a higher concentration of 60.03% [33]. ere is a slight difference in the chemical composition of the main components of the two EOs with those of literature studies, and this may be due to abiotic factors such as the specific climate of the origin regions of the samples.…”
Section: Chemical Composition Of Eossupporting
confidence: 87%
“…Additionally, different studies have demonstrated the antimicrobial activities of oregano EOs against bacterial strains with medical relevance [ 136 , 137 , 138 ]. Despite the antioxidant activities, recent studies have demonstrated their antidiabetic, anti-inflammatory, and cytotoxic activities against cancer cell lines [ 47 , 131 , 139 , 140 ].…”
Section: Bioactive Compounds From Eos Of Spice Plantsmentioning
confidence: 99%
“…Regarding the antimicrobial activities, the EO of different oregano species has shown inhibitory activities against bacterial and fungal strains, which indicates their potential application in the food industry as a preservative [ 149 , 150 ]. The antimicrobial activity has been pointed out due to the synergic effect of constituents of oregano EO and fractions, especially when carvacrol and thymol are present [ 140 ].…”
Section: Bioactive Compounds From Eos Of Spice Plantsmentioning
confidence: 99%
“…One mL of this mother solution was added to a new 25 mL volumetric flask and filled to the mark with methanol, creating a diluted solution. The solutions were placed in 4.0 mL cuvettes (75 µL of clarified juices dilutions and 3 mL DPPH solution), and left to react for 16 min before being read by the spectrophotometer (Model DR 500, Hach Lange GmbH, Düsseldorf, Germany) at 515 nm [ 37 ]. All measurements were made in triplicates with a calibration curve of Trolox at varying concentrations from 5 to 200 ppm.…”
Section: Methodsmentioning
confidence: 99%